2017
DOI: 10.3390/w9110901
|View full text |Cite
|
Sign up to set email alerts
|

The Zeolite-Anammox Treatment Process for Nitrogen Removal from Wastewater—A Review

Abstract: Water quality in San Francisco Bay has been adversely affected by nitrogen loading from wastewater treatment plants (WWTPs) discharging around the periphery of the Bay. While there is documented use of zeolites and anammox bacteria in removing ammonia and possibly nitrate during wastewater treatment, there is little information available about the combined process. Though relatively large, zeolite beds have a finite ammonium adsorption potential and require periodic re-generation depending on the wastewater ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 73 publications
1
13
0
Order By: Relevance
“…Following the partial restoration of aggregate surface materials in the second stage of the tank reactor study, we took advantage of the apparent layered bacterial biofilms (nitrifier over anammox bacteria on the zeolite aggregate) obtained from the prior flood-drain cycling to examine the nitrate scavenging potential of the zeolite-anammox reactor. As others using anammox reactors have noted (Mansell [6]; Grismer and Collison [7]), we found that the continuous submergence of the zeolite media in the tank favored anammox growth over nitrifiers, while the lack of a carbon source limited the growth of denitrifiers, likely promoting the DRNA reactions while efficiently cultivating bio-zeolite for use in seeding other zeolite-anammox reactors. Encouraging the apparent anammox DRNA reactions provided interesting results and has important ramifications for treating wastewaters subject to both ammonium and total nitrogen (TN) discharge limits.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Following the partial restoration of aggregate surface materials in the second stage of the tank reactor study, we took advantage of the apparent layered bacterial biofilms (nitrifier over anammox bacteria on the zeolite aggregate) obtained from the prior flood-drain cycling to examine the nitrate scavenging potential of the zeolite-anammox reactor. As others using anammox reactors have noted (Mansell [6]; Grismer and Collison [7]), we found that the continuous submergence of the zeolite media in the tank favored anammox growth over nitrifiers, while the lack of a carbon source limited the growth of denitrifiers, likely promoting the DRNA reactions while efficiently cultivating bio-zeolite for use in seeding other zeolite-anammox reactors. Encouraging the apparent anammox DRNA reactions provided interesting results and has important ramifications for treating wastewaters subject to both ammonium and total nitrogen (TN) discharge limits.…”
Section: Discussionsupporting
confidence: 64%
“…Influent to both the barrel and Baker tank reactors was obtained from 3.4 m 3 (1000 gal) and 30 m 3 (8000 gal) AD filtrate storage-settling tanks, respectively. Both reactors were designed as recirculating trickling-filter reactors and operated as two-layer aerobic-anaerobic treatment systems to take advantage of the nitritation-anammox process described by Zekker et al [12] and the oxycline described in our review (Grismer and Collison [7]). In effect, the two-layer zeolite-anammox system within a single reactor enables the top layer to produce nitrite (equivalent to the Sharon process in a separate tank) while, presumably, a combination of denitrifying and anammox bacteria in the lower submerged layer converts nitrite and ammonia to nitrogen gas.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, treatment methods have emerged exploiting the large cation-exchange capacity of zeolite aggregates; however, some issues remain in upscaling their application in wastewater treatment due to media regeneration requirements. Grismer and Collison [6] provide a more detailed review of the use of zeolites and anammox bacteria in wastewater treatment systems and here we only briefly summarize their observations relevant to domestic wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The negative effects of nutrients (phosphorus-nitrogen) on the receiving water resources (rivers and lakes) have been shown and these effects have been covered by adequate scientific studies (Converti et al, 2009, Kong et al,. 2010, Mata et al, 2010, Bernard, 2011, Abdel-Raouf et al, 2012, Samorì et al, 2013, Kim et al, 2014, Mark and Robert, 2017, Ghawi, 2017and Ghawi, 2018. Therefore, the legislations that define the specifications of treated water for water sources have been established, thus ensuring the safety and preservation of these sources.…”
Section: Introductionmentioning
confidence: 99%